The impact of country-of-origin and brand origin Image in brand equity and purchase intentions : a study on the Portuguese Smartphone Industry - Costa, Francisco Figueiredo Moniz de Figueiredo (2017)
The era of globalization that the world faces, has transcended towards its markets, leading to an increase in competition for global brands. Nowadays, for a brand to stand out from the rest, it must build up a favorable brand equity, thus driving purchase intent by consumers. A way that brands have done so previously, was by using the image of its origins of its products as non-marketing mix elements. This dissertation’s purpose relies on describing the relationships of Country-of-Origin and Brand Origin Image in Brand Equity Dimensions, Brand Equity and ultimately, Purchase Intentions. To achieve so, the perceptions of consumers towards their Smartphone brands in the Portuguese market were examined. The study’s main findings conclude that Brand Equity is constituted by four dimensions, Brand Distinctiveness, Perceived Quality, Brand Loyalty and Brand Awareness, and that Brand Origin Image impacts all these dimensions positively, while Country-of-Origin Image only impacts Brand Distinctiveness and Brand Loyalty. Another crucial finding concerns the direct impact of Brand Origin Image in Brand Equity. In addition, the impact in the relationships of Country-of-Origin and Bran Origin Image with Purchase Intentions was non-existent. Concerning the implications suggested by this study, Smartphone manufacturers should pay attention to the previous mentioned Brand Equity Dimensions, by strengthening their brand equity with a sense of uniqueness and positive distinction, while raising favorable brand awareness, delivering good quality products and retaining loyal customers. Finally, it is concluded that an efficient mean to achieve the previous objectives is by constructing a favorable Brand Origin Image.